Cher : the memoir, part one - Cher, 1946- (Dey Street, an imprint of WilliamMorrow, 2024)
"After more than seventy years of fighting to live her life on her own terms, Cher finally reveals her true story in intimate detail,in a two-part memoir."--Provided by publisher.